Kepemimpinan Kepala Sekolah Perempuan SMP Negeri Kota Banda Aceh - Musriadi, Musriadi; Jalaluddin, Jalaluddin; Surya, Erdi; Bahri, Saiful (Indo Publishing, 2025)
This study aims to describe the leadership of female principals in public junior high schools (SMP Negeri) in Banda Aceh in developing adaptive, inclusive, and character-based schools. This qualitative reflective study employed in-depth interviews, participant observation, and document analysis. The findings reveal that female principals in Banda Aceh demonstrate collaborative and value-based leadership styles rooted in Islamic spirituality and Acehnese cultural values. Their leadership emphasizes empathy, morality, and professionalism, which foster safe, harmonious, and inspiring school environments. The research concludes that female leadership contributes significantly to school transformation, not only by improving academic and managerial performance but also by strengthening the moral and social character of school communities.